Psychodiabetologie - Albus, Christian; Petrak, Frank (PPmP - Psychotherapie · Psychosomatik · Medizinische Psychologie, 2021)
Patienten mit Diabetes mellitus vom Typ 1 oder 2 benötigen relativ häufig eine psychotherapeutische oder psychopharmakologische Behandlung im Zusammenhang mit ihrer Erkrankung, z. B. wegen Problemen mit der Krankheitsbewältigung und/oder einer psychischen Komorbidität. Beide Anlässe sind oft verknüpft mit diabetes-spezifischen Problemen, aber auch mit Folge- oder Begleiterkrankungen.People affected by diabetes mellitus often have difficulties coping with their condition. This can be further worsened by psychological co-morbidities (e. g., depression or anxiety disorders). Both factors are associated with diabetes-specific problems (e. g., persistent hyperglycaemia, recurrent hypoglycaemia), but also with diabetes complications or comorbid somatic diseases. When psychotherapeutic or psychopharmacological treatment is indicated, it is essential to take into account the particularities of diabetes and the different types of diabetes. This review focuses on adults only and includes a brief description of the clinical features and therapeutic goals in diabetes mellitus. Critical diabetic symptoms that should result in specific interventions (yellow flags) as much as symptoms that require immediate intervention (red flags) are highlighted. Finally, psychological and behavioural factors as well as mental comorbidities that are relevant to the management of diabetes mellitus are discussed.
Keywords: Diabetes mellitus; psychological factors; mental comorbidity; diagnostics; therapy